EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF STAD MENGGUNAKAN ALAT PERAGA ALQURAN UNTUK MENINGKATKAN PENGUASAAN TAJWID - Muhammad Habibbulloh; Ali Arifin (Jurnal Pendidikan Agama Islam, 2019)
Tajweed mastery is an absolute requirement in reading the Al-Qur’an properly and correctly. Without the mastery of the knowledge of recitation, reading the Al-Qur’an surely and correctly only becomes impossible. The aim of this research are tested and evaluated the effectivity of learning model cooperative with STAD type using tool kit of Al-Qur’an to increasing mastery of tajweed nun sukun and tanwin student of elementary school. The sample was taken randomly class IV in one of the elementary schools in Mojokerto, East Java, as much 20 students. The design of research used one group pretest-posttest. Collected data of competence test of mastery read Al-Qur’an which consists of tajweed nun sukun and tanwin law in pretest and posttest. Data analyzed by descriptive quantitative, normality test and t-test, and N-gain. The finding of research among sample of research distribute in normal form, analyze of t-test showed that there were significant differences between pretest and posttest, and N-gain showed that increasing of score posttest categorized High. Based on the findings of the research, conclude that learning model cooperative with STAD type using tool kit of Al-Qur’an effective to increase elementary school students’ mastery of tajweed nun sukun and tanwin law.